The usefulness of three-dimensional ultrasound fusion imaging for precise needle placement in liver thermal ablation: a phantom and an in vivo simulation study - Yuqing Guo; Manying Li; Xiaoer Zhang; Xiaohua Xie; Yanling Zheng; Ming Xu; Ming Kuang; Kaixin Yu; Xiaoyan Xie; Guangliang Huang (International Journal of Hyperthermia, 2022)
Purpose To investigate the value of three-dimensional ultrasound fusion imaging (3DUS-FI) in real-time guiding needle placement by phantom models and in vivo simulations.Materials and methods Two radiologists (beginner and expert) performed needle placement using two-dimensional ultrasound (2DUS) and 3DUS-FI, respectively. In the phantom study, single-needle placement was performed by puncturing the center point of each ball and assessed based on the specimen length. Multiple-needles placement was performed by placing three needles in each ball, and their locations were confirmed by computed tomography, and assessed based on the distance deviation between needles. In the in vivo simulation study, simulated-needle placement was performed by placing a virtual ablation needle in each liver tumor and assessed by the simulated ablative cover rate and margin.Results Specimen length was significantly longer with 3DUS-FI in the beginner, whereas no significant difference was observed in the expert (2DUS vs. 3DUS-FI: beginner, 14.60 ± 2.60 mm vs. 16.25 ± 1.38 mm, p = .017; expert, 16.78 ± 1.40 mm vs. 16.95 ± 1.15 mm, p = .668). Distance deviation between needles was significantly smaller with 3DUS-FI (2DUS vs. 3DUS-FI: beginner, 25.06 ± 16.07 mm vs. 3.72 ± 1.99 mm, p < .001; expert, 11.70 ± 7.79 mm vs. 2.89 ± 1.52 mm, p < .001). The simulated ablative cover rate and margin were significantly larger with 3DUS-FI for the beginner, whereas only the latter was significantly larger for the expert (2DUS vs. 3DUS-FI: beginner, 73.55 ± 8.73% vs. 81.38 ± 11.84%, p = .001, 0.82 ± 0.97 mm vs. 2.65 ± 1.23 mm, p < .001; expert, 78.60 ± 9.91% vs. 83.24 ± 11.69%, p = .059; 1.65 ± 1.15 mm vs. 2.95 ± 1.13 mm, p < .001).Conclusions 3DUS-FI is useful for real-time guiding precise needle placement and may be further use to improve the efficacy of liver thermal ablation.